Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Solve for r: h^2+(pie)r=K

  1. Aug 28, 2011 #1
    1. The problem statement, all variables and given/known data

    solve for r: h^2+(pie)r=K

    2. Relevant equations

    not sure

    3. The attempt at a solution

  2. jcsd
  3. Aug 28, 2011 #2
    This is correct if you mean r=(k-h^2)/(pi)

    r=\frac{k-h^2}{\pi} [/tex]

    [edit] no e in pi... ;)
  4. Aug 28, 2011 #3

    Ray Vickson

    User Avatar
    Science Advisor
    Homework Helper

    This is incorrect: you have written [tex] r = K - \frac{h^2}{\pi}, [/tex] at least when read according to *standard rules*. If you mean that
    [tex] r = \frac{K - h^2}{\pi} ,[/tex] then you need to use brackets: r = (K - h^2)/pi.

Share this great discussion with others via Reddit, Google+, Twitter, or Facebook